FACTORS OF COMPLIANCE, NEGOTIATION, MORAL, PROFIT MANAGEMENT, FISCAL POLICY IN EXECUTING TAX OBLIGATIONS (Case research on MSME processing industry in Mojokerto) - Hartono Hartono; Nersiwad Nersiwad; Fachrudy Asj’ari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research aims to analyze how the behavior of MSME taxpayers in carrying out their tax obligations. The research population is MSME taxpayers domiciled in Mojokerto. The sample of this research involved 42 respondents using the purposive sampling method, questionnaire as an instrument, and processed using SEM approach Warp PLS 6.0. The results show that taxpayer compliance behavior, taxpayers' willingness to negotiate, and provision of financial statements based on earnings management positively impact tax obligations as measured by the amount of voluntary tax compliance. Still, the tax morale of taxpayers has a negative impact on tax obligations incurred, calculated based on the value of voluntary tax compliance, taxpayer compliance behavior, the willingness of taxpayers to negotiate, provision of financial reports based on earnings management mediating the perception that MSME fiscal policy has a positive impact on tax obligations as measured by the value of voluntary tax compliance. In contrast, the tax morale of taxpayers is mediated by the perception of MSME's fiscal policy having a negative impact on voluntary tax compliance. Recently, it found that obedient taxpayers in carrying out their tax obligations are influenced by the behavior of taxpayers, not because of regulations. Behavior is seen from economic conditions, finances using a fiscal policy approach for MSMEs, and a conceptual system based on a developing view of the tax policy. . Keywords : Taxpayer Behavior, Tax Obligations, and Voluntary Tax Compliance.